If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + -2(2x + -1) = 5 Reorder the terms: 3 + -2(-1 + 2x) = 5 3 + (-1 * -2 + 2x * -2) = 5 3 + (2 + -4x) = 5 Combine like terms: 3 + 2 = 5 5 + -4x = 5 Add '-5' to each side of the equation. 5 + -5 + -4x = 5 + -5 Combine like terms: 5 + -5 = 0 0 + -4x = 5 + -5 -4x = 5 + -5 Combine like terms: 5 + -5 = 0 -4x = 0 Solving -4x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '-4'. x = 0 Simplifying x = 0
| 3(x+2)-18=3x-14 | | 2p=-9+2p | | 18-6a=4a-4a-4(a+3) | | -8c=48 | | 11x+2=2x | | 2m^2-98=0 | | 22=-4x+38 | | 2(5x+14)=10x+6 | | 31+9f+3f-17=14f+18-2f-4 | | Xm+xn+ym+yn=0 | | m(-1)=4-1-2 | | x^22-8x=12 | | 5x-(x+1)=-4 | | 6n+8n=6n | | (3x-5)+(2x-10)=90 | | 16x^3y-32x^2y+8xy^2=0 | | -3g+g=-2g | | -1+2n=1+n | | 7-4n+2n=42-75 | | 7x+x=7x+9 | | -7m-3=-8m-9 | | 10-7m=-8m+2 | | 4x-5=5x-4 | | 3y+4-y=3+y-7 | | 4p-7=3+6p | | 60x+50y= | | .75x+.25(15-x)=.35(15) | | -5y=4x+8 | | X+2x+7=3x+7 | | (6x+4)=88 | | 8y-y=-12+y | | 1+8m=-7+4m+3m |